Traducción, adaptación y validación del inventario de burnout de Copenhagen para Perú - Hernández Breña, Wilson (2022)
The goal is to adapt and analyze the psychometric properties of the Copenhagen Burnout Inventory (CBI) in workers of the national domestic violence helpline (Peru). Two measurements were taken in the same population (n=160). Translation-back translation was applied. Internal consistency was assessed with Cronbach’s alpha, corrected Item-Total Correlation and omega coefficient. Test-retest was performed in the second measurement. Convergent validity was examined with Pearson correlations with the Secondary Traumatic Stress Scale, the Perceived Stress Scale, and the Fear of Covid-19 Scale. Confirmatory Factor Analysis confirmed that the three-correlated factor model has the best fit. Regarding reliability, adequate coefficients were found (alpha: >.82, omega: >.91 and intraclass correlation: > .66). The CBI scales are correlated with the Secondary Traumatic Stress Scale, the Perceived Stress Scale, and the Fear of Covid-19 Scale, and they are also significantly associated with self-reported health status, but only work-related burnout is associated with self-reported workload. As a result, the CBI shows excellent psychometric properties.